Manajemen Pemasaran Dalam Meningkatkan Mutu Pendidikan - Wawan Hari Subagyo (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2024)
Marketing is an activity that sells and offers products and services that are owned, so that consumers can buy and enjoy the products offered. In the current era of globalization, competition between educational institutions is increasingly attractive and competitive, therefore good marketing activities are needed in order to build a positive image and attract public interest. The "quality" aspect is expected to produce graduates (output) who are highly competitive, able to answer the demands and needs of society in the global era and have the originality of Indonesian culture and the Islamic boarding school itself. The quality philosophy that can be adopted in Islamic boarding schools is Total Quality Management. The value of educational institutions is tested when faced with the wants and needs of today's society. On the one hand, in all matters related to education, there are values ​​that must be built, spread and instilled, but at the same time, as time goes by, educational institutions are subject to market habits that demand to be faced. We continue to create new products in line with further developments and gaining popularity. This research uses a qualitative approach, namely the data source is written words obtained from natural situations. This type of research is a case study. In deciding on a marketing management activity program to improve the quality of education at Bhakti Muda Wiyata Vocational School, several considerations need to be made based on the results of the evaluation and analysis of the implementation of the educational marketing program in the previous year. It can be concluded that the efforts carried out by SMK Bhakti Muda Wiyata are not only focused on quantity but also quality.